Recording injuries among World Cup skiers and snowboarders: a methodological study - Flørenes, T. W.; Nordsletten, L.; Heir, S.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2011)
No long-term injury surveillance programs exist for competitive skiing or snowboarding. The objective of this study was, therefore, to compare different methods to record injuries among World Cup athletes in alpine, freestyle, and cross-country skiing, snowboarding, ski jumping and Nordic combined. Information regarding injuries sustained during the 2006-2007 winter season was recorded through three separate and independent systems: prospective injury reports by technical delegates (TD) from the International Ski Federation, prospective medical team registration by selected teams, and retrospective athlete interviews at the end of the season. A total of 100 unique injuries to 602 World Cup athletes were identified from any of the three recording methods. Of these, 91% were registered through the athlete interviews, 47% by the medical team registration and 27% by the TD reports. Only 20 injuries (20%) were captured by all three methods. A total of 64 time-loss injuries were registered. The interviews captured 60 (94%), the medical team registration 39 (61%), and the TD reports 23 (36%) time-loss injuries, while 18 (28%) were registered by all three systems. Retrospective interviews with athletes/coaches regarding injuries during the last 6 months gave the most complete picture of injuries to World Cup skiers and snowboarders.